Pengaruh Penggunaan Metode Learning Start With A Question (LSQ) Pada Mata Pelajaran Pendidikan Agama Islam Terhadap Hasil Belajar Siswa - Ana Nisa Silvia; Sulaiman Sulaiman (An-Nuha, 2023)
The main topic of this study is the application of the Learning Start With A Question (LSQ) method in the subject of Islamic Religious Education to the learning outcomes of students in class XI IPS 1 and XI IPS 3 at SMA Negeri 3 Pariaman. Based on observations and interviews, it is known that student learning outcomes still relatively low before the implementation of this method. This type of research is quantitative research using correlational research methods with the form of the relationship in this study Bivariat, namely a relationship that involves one independent variable with one dependent variable. The population in this study were class XI IPS 1 and XI IPS 3 totaling 67 students. Based on the results of the analysis that has been carried out, a simple linear regression equation model is obtained Y = 5.235 + 0.781X, which means that if the Learning Start With A Question (LSQ) method is getting better, it will increase by 0.781%. From the results of the analysis of the coefficient of determination (R^2) it is known that the value (R^2) is 0.174 or 17.4%, which means that the Learning Start With A Question (LSQ) method has a contribution to learning outcomes and the remaining 82.6% is influenced by other factors . While the results of the F test analysis obtained the value F_count > F_table (13.705 > 3.10) which means that the Learning Start With A Question (LSQ) method simultaneously has a positive and significant effect on student learning outcomes. While the T test obtained a T_count value of 3.702 > 1.669 meaning that the Learning Start With A Question (LSQ) method partially had a positive and significant effect on student learning outcomes. Based on the data analysis processing, the Learning Start With A Question (LSQ) method can be applied to the teaching and learning process in schools to improve student learning outcomes.